Catalogue of families and their type genera in the mite suborder Uropodina (Acari: Mesostigmata) - Halliday, R. B. (Zootaxa, 2016)
This paper reviews 47 names that have been used at the levels of Family, Subfamily and Tribe, for mites in the suborder Uropodina. Complete bibliographic references are provided for all of these names and the names of their type genera. The spelling and authorship of taxon names is corrected where necessary. Fifteen of these family-group names are unavailable, because they do not satisfy the requirements of the International Code of Zoological Nomenclature. However, some of these names represent taxonomic concepts that may be useful in future revisions of the group.